2023
DOI: 10.3390/nu15020374
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Fat Characteristics and Mortality in Rectal Cancer: A Retrospective Study

Abstract: The aim of this study was to evaluate the association of adipose tissue characteristics with survival in rectal cancer patients. All consecutive patients, diagnosed with stage II–IV rectal cancer between 2010–2016 using baseline unenhanced Computed Tomography (CT), were included. Baseline total, subcutaneous and visceral adipose tissue areas (TAT, SAT, VAT) and densities (TATd, SATd, VATd) at third lumbar vertebra (L3) were retrospectively measured. The association of these tissues with cancer-specific and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Furthermore, the SHAP plot indicates a negative correlation between SATD and OS rate. Similar to our ndings, Pellegrini et al [47] found increased SATD is associated with poorer cancer-speci c survival in rectal cancer; Patrick T. Bradshaw et al [48] found that elevated SAT was associated with worse survival among the women with non-metastatic breast cancer. The associated underlying mechanism may be attributed to the shrinkage, brosis, or in ammation of adipose tissue [49,50].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the SHAP plot indicates a negative correlation between SATD and OS rate. Similar to our ndings, Pellegrini et al [47] found increased SATD is associated with poorer cancer-speci c survival in rectal cancer; Patrick T. Bradshaw et al [48] found that elevated SAT was associated with worse survival among the women with non-metastatic breast cancer. The associated underlying mechanism may be attributed to the shrinkage, brosis, or in ammation of adipose tissue [49,50].…”
Section: Discussionsupporting
confidence: 90%